Endothelin-1 in the failing Fontan: pathobiology, precision therapeutics, and future trial design - Maiza, Iman (Frontiers in Pediatrics, 2026)
The Fontan circulation, devised as definitive palliation for single-ventricle congenital heart disease, imposes systemic venous hypertension, loss of pulmonary arterial pulsatility, and restricted preload reserve. These hemodynamic trade-offs progressively injure the pulmonary vasculature, liver, and lymphatic system, producing late morbidities including elevated pulmonary vascular resistance, Fontan-associated liver disease (FALD), protein-losing enteropathy, and arrhythmias. Endothelin-1 (ET-1), a potent vasoconstrictor and profibrotic mediator, plausibly unifies these complications. Mechanistic studies demonstrate ET-1 upregulation in failed Fontan lungs, activating PLC–Ca2+, RhoA/ROCK, and MAPK/ERK cascades to drive vasoconstriction and remodeling. In cirrhotic livers, ET-1 localizes to stellate cells, promoting contraction and fibrogenesis, mechanisms biologically relevant to congestive FALD. Clinical cohorts consistently show elevated ET-1 correlating with hospitalization, exercise intolerance, and arrhythmias. Trials of endothelin-receptor antagonists (bosentan, ambrisentan, macitentan) demonstrate reassuring safety and suggest benefit when outcomes emphasize ventilatory efficiency or hepatic endpoints rather than peak oxygen consumption, which is physiologically constrained in Fontan physiology. Given the mixed results of existing trials, a framework is outlined that stratifies Fontan patients into pulmonary-inefficiency, congestive-hepatic, lymphatic, and arrhythmia-dominant phenotypes, using co-primary endpoints such as VE/VCO2 slope, elastography, and biomarker panels. By linking ET-1 biology to pragmatic trial design, this approach emphasizes targeted strategies that may stabilize the circulation, extend transplant candidacy, and improve long-term outcomes.